POTENSI PERLUASAN PERMINTAAN PERJALANAN PADA WILAYAH SEKITAR INTEGRASI RUTE LRT JAKARTA DAN TRANSJAKARTA KORIDOR 4 - Thanra, Savita
Integration of public transportation modes have been one of the main focus and concerns regarding the planning and development of the modes and infrastructures needed to deal with heavy congestion problems at DKI Jakarta. One of the existing forms of public transportation integration is the integration of LRT Jakarta and Transjakarta corridor 4. Since the skybridge that connects the two modes were built, the integration of the routes of both modes has a total of 18 stations operating and passing by several sub-districts. The route-integration of 2 different public transportation modes unfold potentials of demand expansion on the surrounding sub-districts. There is yet a study that discusses the impact of the route-integration of LRT Jakarta and Transjakarta corridor 4 towards the expansion of potentials of demand on the surrounding sub-districts. This research uses 3 types of analysis that take into account several aspects of demand potential appraisals. Classification of potential demand criterion fulfillments could indicate the potential demand locations on the surrounding sub-districts, the accessibility index could indicate which sub-district has the highest degree of accessibility, and the location-allocation analysis could indicate which stations have better performances at allocating demands and which sub-district has the optimal location to accommodate new stations to increase demand allocation. Based on the resut of all 3 points of analysis, 3 sub-districts are identified to have the highest demand potential expansion which are : sub-district Pulogadung, Tanah Abang and Tebet. The findings of the study could serve as the reference for future infrastructure and feeder-routes replenishment to optimize the role of public transportation to respond to the potential demands of society in the surrounding areas and in general.